Effects of breast feeding on neuropsychological development in a community with methylmercury exposure from seafood - Jensen, Tina Kold; Grandjean, Philippe; Jørgensen, Esben Budtz; White, Roberta F; Debes, Frodi; Weihe, Pál (Journal of exposure analysis and environmental epidemiology, 2005)
Breastfeeding has been associated with an advantage to infant neurobehavioral development, possibly in part due to essential nutrients in breast milk. However, breast milk may be contaminated by environmental neurotoxicants, such as methylmercury. In the Faroe Islands, where maternal consumption of pilot whale may cause transfer of marine toxicants into breast milk, a cohort of 1022 consecutive singleton births was generated during 1986–87. Methylmercury exposure was assessed from mercury concentrations in cord blood and in the hair of the child at age 12 months, and the duration of breastfeeding was recorded. At approximately 7 years of age, 917 (90%) of the children underwent detailed neurobehavioral examination. After adjustment for confounders, breastfeeding was associated with only marginally better neuropsychological performance on most tests. These associations were robust even after adjustment for cord-blood and hair mercury concentration at age 1 year. Thus, in this cohort of children with a relatively high prenatal toxicant exposure and potential exposure to neurotoxicants through breast milk, breastfeeding was associated with less benefits on neurobehavioral development than previously published studies though not associated with a deficit in neuropsychological performance at age 7. Although the advantage may be less, Faroese women can still safely breastfeed their children.